2018
DOI: 10.1021/acs.analchem.8b04179
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for In Situ Imaging of Cellular Alkaline Phosphatase Activity Using Gold Nanoflower Probe and Localized Surface Plasmon Resonance Technique

Abstract: In this work, a simple and ultrasensitive localized surface plasmon resonance (LSPR) method that use Au nanoflowers (AuNFs) as a probe was designed for in situ monitoring of alkaline phosphatase (ALP) activity. The AuNFs were fabricated by hydrogen tetrechloroaurate-induced oxidative disruption of polydopamine-coated Au nanoparticles (AuNPs), and subsequently, growth of Au nanopetals on AuNPs occurred. The as-prepared AuNFs showed a much higher LSPR capability and stronger scattering color change than AuNPs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 50 publications
(73 reference statements)
1
38
0
Order By: Relevance
“…With the aid of spectrometer, the individual dark‐field scattering spectrum of single plasmonic nanostructure can be obtained, which is contributed to the biosensing and diagnostic at the single particle/cell level [61]. It is reported that deposition of Ag on the Au nanoflowers (AuNFs) surface could be used for in situ monitoring of alkaline phosphatase (ALP) activity (Figure 7a) [62]. The deposition of Ag shell changed the morphology of AuNFs, leading to the tremendous LSPR response and scattering color change, which was related to ALP activity.…”
Section: Dark‐field Light‐scattering Microscopymentioning
confidence: 99%
“…With the aid of spectrometer, the individual dark‐field scattering spectrum of single plasmonic nanostructure can be obtained, which is contributed to the biosensing and diagnostic at the single particle/cell level [61]. It is reported that deposition of Ag on the Au nanoflowers (AuNFs) surface could be used for in situ monitoring of alkaline phosphatase (ALP) activity (Figure 7a) [62]. The deposition of Ag shell changed the morphology of AuNFs, leading to the tremendous LSPR response and scattering color change, which was related to ALP activity.…”
Section: Dark‐field Light‐scattering Microscopymentioning
confidence: 99%
“…Sappia et al (2017) researched SPR for the real time detection of ALP by using WGA-modified surfaces, where ALP absorbs and the signal increases [90]. Wang et al (2018) created a probe using gold nanoflower in detecting cellular ALP and found that the ALP activity could be detected up to limits of about 0.03 μU L −1 [91]. In addition, the ALP activity of the mammalian cells was able to be attracted using the develop probe.…”
Section: Optical Detection Techniquesmentioning
confidence: 99%
“…20,21 Although silver coating is beneficial for signal enhancement of Au@Ag NPs, some problems related to the surface topography variation exist. Silver randomly grew on the cores without any site and density regulation, which tended to smooth the surface of core NPs, merging the tips, holes, or junctions of the core NPs (especially for nanoflowers 22 and nanostars 10 ). Thus, the resultant bimetallic NPs were usually spherical and smooth and lost the intrinsic hotspots of the cores.…”
Section: ■ Introductionmentioning
confidence: 99%